Decoding Wellness: Critical Architecture of Health Literacy Integration in Global Science Instruction - Anifatur Rosidah; Laifa Rahmawati (Assyfa Learning Journal, 2026)
Health literacy is a vital competency that enables individuals to access, understand, evaluate, and apply health information for informed decision-making. Integrating health literacy into natural science education provides a strategic avenue for fostering these competencies early in formal schooling. This Systematic Literature Review (SLR) synthesizes empirical studies published between 2017 and 2026 from Scopus, ERIC, and SINTA-accredited journals to map instructional strategies, science learning contexts, and research trajectories. Following the PRISMA 2020 protocol with a SPIDER framework, 30 articles were selected from 3,734 initial records. Findings demonstrate that health literacy integration is predominantly conducted at secondary education levels using quasi-experimental and mixed-methods designs. The primary pedagogical strategies comprise project-based and inquiry learning, media-based interventions (videos, websites, virtual reality), collaborative learning, and immersive programs. The dominant science topics leveraged as learning contexts include nutritional literacy, reproductive health, oral health, mental health, and infectious disease prevention. Overall, health literacy integration consistently enhances students' health knowledge, awareness, and decision-making skills, though sustained health behavior change remains challenging. Future research should emphasize longitudinal designs, context-sensitive implementation in under-resourced schools, and the development of standardized K–12 health literacy assessment instruments.